2024
DOI: 10.3390/wevj15030108
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Potential Use of Electric Vehicles in Urban Areas: A Real-Life Survey-Based Study in Hail, Saudi Arabia

Abdulmohsen A. Al-fouzan,
Radwan A. Almasri

Abstract: This study aimed to uncover the attitudes, preferences, and perceptions of Hail residents toward electric vehicles (EVs) by employing a real-life survey-based approach. This paper presents an in-depth analysis of the potential adoption and impact of EVs to clarify the picture of the transition from using traditional vehicles to using EVs in Hail City, Saudi Arabia. Hail is rapidly becoming a more urbanized city; in the past few decades, the city’s area has expanded from 3242 to 17,526 hectares, and its populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…This suggests that interest in EVs is expanding, which is consistent with research by Almutairi [15]. To obtain more data about citizens' behavior regarding EVs and their CSs in Hail, see Al-fouzan and Almasri [12].…”
Section: Societal and Behavioral Parameterssupporting
confidence: 67%
See 3 more Smart Citations
“…This suggests that interest in EVs is expanding, which is consistent with research by Almutairi [15]. To obtain more data about citizens' behavior regarding EVs and their CSs in Hail, see Al-fouzan and Almasri [12].…”
Section: Societal and Behavioral Parameterssupporting
confidence: 67%
“…EV consumers' attitudes and views have been the subject of numerous research studies. To offer insight into the potential adoption and impacts of EVs in Hail City, KSA, as well as the move away from conventional cars, Al-fouzan and Almasri [12] conducted a survey. With 37.9% of participants stating they would be pleased to switch to an EV and 78.6% of participants knowing where EV charging stations are, the results show a clear preference for EVs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Sheldon and Dua [61] found that over 70% of respondents reported traveling 10 to 60 km each day. Al-fouzan and Almasri [62] completed a survey to shed light on the possible uptake and effects of EVs in Hail City, Saudi Arabia, and the shift away from conventional cars. The findings indicate a strong preference for EVs, with 37.9% of participants saying they would be happy to convert to an EV and 78.6% of participants knowing where EV charging stations are.…”
Section: User Behavior and Adoption Of Solar-powered Ev Chargingmentioning
confidence: 99%